2019
DOI: 10.1186/s12879-019-4657-0
|View full text |Cite
|
Sign up to set email alerts
|

The Safe Start trial to assess the effect of an infant hygiene intervention on enteric infections and diarrhoea in low-income informal neighbourhoods of Kisumu, Kenya: a study protocol for a cluster randomized controlled trial

Abstract: BackgroundSymptomatic and asymptomatic enteric infections in early childhood are associated with negative effects on childhood growth and development, especially in low and middle-income countries, and food may be an important transmission route. Although basic food hygiene practices might reduce exposure to faecal pathogens and resulting infections, there have been few rigorous interventions studies to assess this, and no studies in low income urban settings where risks are plausibly very high. The aim of thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 21 publications
(20 reference statements)
0
28
0
Order By: Relevance
“…Our results also emphasized that Schools/Kindergartens have patterns of good hygiene practices associated with utensils, supported by the absence of E. coli and the highest proportion of samples with mesophilic microorganisms below 100 CFUs. A recent study reported that appropriate food hygiene interventions among child caregivers of weaning infants, focused on safe hand hygiene, safe food preparation and storage, as well as safe feeding, can reduce foodborne exposure to enteric pathogens [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also emphasized that Schools/Kindergartens have patterns of good hygiene practices associated with utensils, supported by the absence of E. coli and the highest proportion of samples with mesophilic microorganisms below 100 CFUs. A recent study reported that appropriate food hygiene interventions among child caregivers of weaning infants, focused on safe hand hygiene, safe food preparation and storage, as well as safe feeding, can reduce foodborne exposure to enteric pathogens [38].…”
Section: Discussionmentioning
confidence: 99%
“…Our intervention resulted in substantial improvements in hygienic food preparation areas (outcome 1) and safe storage of food (outcome 2). Though food is one of the most critical pathways for children to be exposed to faecal pathogens, 48 food hygiene interventions are underemphasised in WASH and nutrition programming, and few studies have measured the impact of any 49 Food hygiene presented a contextual challenge related to the larger sociocultural realities of caretakers. 50 In addition, different high-risk foods require different food hygiene strategies; for example, if milk is the primary vector for food-related pathogens, 51 it would require a different type of hazard mitigation than porridge.…”
Section: Discussionmentioning
confidence: 99%
“…These densely populated wards are characterized by lack of improved sanitation facilities, use of county-provided water points, poor housing, and high rates of poverty. The Safe Start study evaluates the effect of a food hygiene intervention targeting early childhood exposure to enteric pathogens through contaminated food (ClinicalTrials.gov ID: NCT03468114) 15 . The protocol includes a midline visit at 8 months of age to observe the caregiver prepare food and feed the child, and to take a food sample for microbial testing.…”
Section: Methodsmentioning
confidence: 99%
“…Formative research on caregiver experiences and infant food safety 7 16 , and the challenges for Community Health Volunteers (CHVs) in delivery of health care information 17 informed study design. The design of the Safe Start intervention was optimized through an interactive pilot study 18 and CHVs were involved in the implementation of the study 15 . Community knowledge dissemination meetings were convened after the study to discuss results with the community.…”
Section: Methodsmentioning
confidence: 99%